2016
DOI: 10.5194/acp-16-7523-2016
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of moisture transport on drifting snow sublimation in the saltation layer

Abstract: Abstract. Drifting snow sublimation (DSS) is an important physical process related to moisture and heat transfer that happens in the atmospheric boundary layer, which is of glaciological and hydrological importance. It is also essential in order to understand the mass balance of the Antarctic ice sheets and the global climate system. Previous studies mainly focused on the DSS of suspended snow and ignored that in the saltation layer. Here, a drifting snow model combined with balance equations for heat and mois… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…This model is applicable for occurrent snowfall event or early stage after a snowfall event so far. The drifting snow sublimation (Dai & Huang, ; Huang & Shi, ; Huang et al, ; Pomeroy et al, ) in both saltation and suspension layer is planned to introduce into the model in a future version. Remote sensing data and Snowpack model are also our future outlook (Figure ), to make the model more comprehensive for regional hydrological research.…”
Section: Discussionmentioning
confidence: 99%
“…This model is applicable for occurrent snowfall event or early stage after a snowfall event so far. The drifting snow sublimation (Dai & Huang, ; Huang & Shi, ; Huang et al, ; Pomeroy et al, ) in both saltation and suspension layer is planned to introduce into the model in a future version. Remote sensing data and Snowpack model are also our future outlook (Figure ), to make the model more comprehensive for regional hydrological research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sublimation associated with these layers is not accounted for. Other studies have shown that drifting snow sublimation within the salutation layer can be very significant (Huang et al, 2016). There is a further point to be made with respect to clouds that relates to (5).…”
Section: Error Analysismentioning
confidence: 98%
“…However, although numerous experimental (Bintanja, ; Mann et al, ; Schmidt, ; Wever et al, ) and theoretical studies (Déry & Yau, ; Groot Zwaaftink et al, ; Vionnet et al, ; Xiao et al, ) on drifting snow sublimation have been conducted, sublimation of drifting snow within the saltation layer (the near‐surface layer in which most particles move in characteristic ballistic hops) is only rarely investigated (Dai & Huang, ; Huang et al, ; Sharma et al, ) as the air humidity near the surface saturates rapidly when drifting snow occurs because of a high snow concentration (Bintanja, , ; Mann et al, ). However, because of moisture transportation, there are always slight deviations from the saturated state, which give rise to snow sublimation, and the impact of such deviations has not yet been quantified.…”
Section: Introductionmentioning
confidence: 99%